Estimation of SH-Wave Amplification in the Bandung Basin Using Haskellâs Method - A. Afnimar (Journal of Engineering and Technological Sciences, 2014)
The Bandung basin is a large basin in Indonesia surrounded by mountains that are associated with faults. There is the possibility of earthquakes generated by these faults shaking populated areas in the basin. The consequences will be worse because the shaking is amplified by the sediment layer of the basin. We have estimated the amplification of SH-waves generated by the Lembang fault using Haskell's method for multilayer models. The pattern of amplification is a decreasing value with increasing distance from the Lembang fault. This pattern is valid for low-frequency incident waves. For higher-frequency incident waves, the pattern looks more complicated. Fortunately, there are many areas with low amplification values. Hopefully, this result will help the local government in making decisions regarding construction planning in this region. Of course, the final objective is to reduce earthquake risks.